Culture, Commerce and Value: The Contemporary South African Fine Art Market in Relation to Concepts of Artistic and Financial Success - le Clus-Theron, Jean (Michaelis School of Fine Art, 2025)
In this study I investigate two main premises: firstly that art intermediaries are imperative in value creation in an artist's career, and secondly that high prices are used as a way to justify, measure or reflect an artist's “importance”. The motives for these investigations are, firstly, that there would seem to be insufficient academic research on these notions in the South African art scene, and secondly, the existence of a counter argument, namely, that the high prices attained on the art market may be deemed arbitrary and irrational. This study investigates the South African contemporary fine art scene along with the role of South African art intermediaries and their perceptions on ideas of “importance” and “success”, using two case studies. These case studies comprise the career trajectories of two living artists residing in South Africa, who compared to all other living artists residing in South Africa, have attained the highest prices in their careers for work on auction, namely, William Kentridge and Dylan Lewis. In this study twenty-six intermediaries were interviewed and the ensuing data used to investigate how these and other intermediaries influence perceptions of the importance and success of these artists' work. This dissertation incorporates Pierre Bourdieu's theory of field, capital and distinction, and uses Alan Bowness's four conditions of success as a framework for investigation.